2013
DOI: 10.1007/s10551-013-1911-z
|View full text |Cite
|
Sign up to set email alerts
|

Positive Organizational Ethics: Cultivating and Sustaining Moral Performance

Abstract: We present this special issue on positive organizational ethics (POE) to highlight those pursuing positive subjective experiences, positive attributes of individuals and groups, and positive practices that contribute to ethical and virtuous behavior in organizations. Although prior research has offered some insight in this area, there is still much to be learned about how to cultivate and sustain ethical strength in different types of organizations and how goodness can emerge from and in spite of human failing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 43 publications
0
27
0
2
Order By: Relevance
“…Rather, they can be ''complementary'' in that firms can ''do well by doing good.'' Moreover, since ethical compliance is a moral minimum, virtuous organizations emphasize nurturing moral development and ethical strength to ensure that they not only prevent unethical actions, but also promote virtuous behaviors (Sekerka et al 2014). Having a clearer understanding of why companies practice SSCM adds significantly to our knowledge of how to better advance corporate sustainability.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, they can be ''complementary'' in that firms can ''do well by doing good.'' Moreover, since ethical compliance is a moral minimum, virtuous organizations emphasize nurturing moral development and ethical strength to ensure that they not only prevent unethical actions, but also promote virtuous behaviors (Sekerka et al 2014). Having a clearer understanding of why companies practice SSCM adds significantly to our knowledge of how to better advance corporate sustainability.…”
Section: Resultsmentioning
confidence: 99%
“…Moral organizations emphasize moral development and ethical strength to ensure that they not only prevent unethical actions but also promote "do well by doing good" behavior (Sekerka, Comer, & Godwin, 2014 Third, the longer duration of the green project is, the stronger green motives are. According to deontological theory, companies with moral motives engage in green activities because it is the right thing to do and to more effectively care for environment.…”
Section: Discussionmentioning
confidence: 99%
“…Fray [89], Payne and Raiborn [90]) which highlighted the link between ethics and sustainable development, for example, the focus on the impact of ethics on behavior in terms of social responsibility and sustainable development [89]. Since organizations may have questions about how to create organizational ethics, previous studies maintain that the development of an ethical culture together with the ethical climate, produces organizational ethics [53]. Ethical climate and culture in the organization encourage its members to act correctly in accordance with the understanding of ethics.…”
Section: Discussionmentioning
confidence: 99%
“…This paper sheds light on the importance of organizational ethics in sustainable development, while previous studies have shown that the achievement of sustainable development goals is affected by the intention of employees to act ethically. Employees' intention to behave ethically to serve sustainable development goals may depend on the extent to which they perceive their organizational ethics [52,53]. A study by Koh and Boo [54] states that the ethical climate and ethical culture are related aspects of organizational ethics.…”
Section: Organizational Ethicsmentioning
confidence: 99%